2014
DOI: 10.1371/journal.pone.0109570
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Amino Acids Physico-Chemical Properties and Usage of Late Embryogenesis Abundant Proteins, Hydrophilins and WHy Domain

Abstract: Late Embryogenesis Abundant proteins (LEAPs) comprise several diverse protein families and are mostly involved in stress tolerance. Most of LEAPs are intrinsically disordered and thus poorly functionally characterized. LEAPs have been classified and a large number of their physico-chemical properties have been statistically analyzed. LEAPs were previously proposed to be a subset of a very wide family of proteins called hydrophilins, while a domain called WHy (Water stress and Hypersensitive response) was found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 66 publications
1
18
0
Order By: Relevance
“…The LEA14 pear homolog was confirmed to belong to the group 5C proteins of the LEA family, as shown in the phylogenetic tree analysis, and it was designated as PcLEA14 . Group 5C proteins have a unique structure [ 9 , 10 , 11 ], and although their role is unclear, they have been the subject of a small number of studies. An earlier study reported that overexpression of the same gene group in maize, ZmLEA5C , improved low-temperature stress tolerance in tobacco plant [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The LEA14 pear homolog was confirmed to belong to the group 5C proteins of the LEA family, as shown in the phylogenetic tree analysis, and it was designated as PcLEA14 . Group 5C proteins have a unique structure [ 9 , 10 , 11 ], and although their role is unclear, they have been the subject of a small number of studies. An earlier study reported that overexpression of the same gene group in maize, ZmLEA5C , improved low-temperature stress tolerance in tobacco plant [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…LEA proteins are classified into seven groups according to their amino acid sequences; however, group 5 proteins are considered atypical LEA proteins because of their comparatively large number of hydrophobic residues and their lack of common sequences and important motifs found in other LEA proteins [ 8 ]. Group 5C proteins have a Water Stress and Hypersensitive (WHy) response domain, and their function is expected to differ from that of other LEA proteins [ 9 , 10 , 11 ]. Although some studies have investigated the stress response of group 5C LEA proteins in herbaceous plants [ 2 , 12 , 13 , 14 ], there is limited information available on trees in which a unique functionality of the gene is expected to ensure perennially.…”
Section: Introductionmentioning
confidence: 99%
“…The original grouping of LEA proteins is based on common structural features, which were first identified in the prototypical cotton plant (G. hirsutum) (11), but subsequent alternative classifications have led to large inconsistencies with respect to the original taxonomy (23). LEA proteins have been variously assigned to three major groups associated with their taxonomic origins, i.e., plants, bacteria, and vertebrates (22), while other classifications yield five (23) or seven (21) major groups, with nine to 14 LEA subgroups (16,(24)(25)(26). The different classification structures have been based on the analysis of transcripts (27,28), amino acid sequences and conserved motifs (26,29,30), three-dimensional protein structures, or chemical characteristics, including in silico analyses of protein or oligonucleotide probability profiles (POPP) (16,22,23,25,26,(29)(30)(31)(32)(33).…”
Section: Classification Of Lea Proteinsmentioning
confidence: 99%
“…A set of the DHNs are called hydrophylins because of their specific response to osmotic stress (Garay-Arroyo et al, 2000; Jaspard and Hunault, 2014). Hydrophylins play important role in protecting cell components from the adverse effects caused by low water availability due to biochemical properties such as high Glycine (Gly) content (> 6%) and low grand average hydropathy (GRAVY) (< -1) (Garay-Arroyo et al, 2000; Battaglia et al, 2008;Reyes et al, 2008).…”
Section: Dehydrin: Functional Diversification Via Biochemical Structmentioning
confidence: 99%